Acinetobacter baumannii Sampled from Cattle and Pigs Represent Novel Clones - Valeria Mateo-Estrada; Leila Vali; Ahmed Hamouda; Benjamin A. Evans; Santiago Castillo-Ramírez (Microbiology Spectrum, 2022)
ABSTRACT Acinetobacter baumannii is a very important human pathogen. Nonetheless, we know very little about nonhuman isolates of A. baumannii. Here, we determine the genomic identity of 15 Scottish cattle and pig isolates, as well as their antibiotic and virulence genetic determinants, and compare them with 148 genomes from the main human clinical international clones. Our results demonstrate that cattle and pig isolates represent novel clones well separated from the major international clones. Furthermore, these new clones showed fewer antibiotic resistance genes and may have fewer virulence genes than human clinical isolates. IMPORTANCE Over the last decades, huge amounts of information have been obtained for clinical isolates of A. baumannii and the clones they belong to. In contrast, very little is known about the genomic identity and the genomic basis for virulence and resistance of animal isolates. To fulfil this gap, we conducted a genomic epidemiology study of 15 Scottish cattle and pig isolates in the context of almost 150 genomes belonging to the main international clones of A. baumannii. Our findings show that these animal isolates represent novel clones clearly different from the major international clones. Furthermore, these new clones are distinct in nature considering both antibiotic resistance and virulence when compared with their human clinical counterparts.